Pengaruh Aplikasi TikTok terhadap Minat Belajar Siswa Geografi pada Kelas XI SMA Muhammadiyah 09 Kualuh Hulu Kabupaten Labuhan Batu Utara - Warlina, Warlina; Febriandi, Febriandi (ALSYS, 2024)
The purpose of this study is to find out whether the TikTok application affects students' interest in learning geography subjects at SMA Muhammadiyah 09 Kualuh Hulu, North LabuhanBaatu Regency. This study uses quantitative research on the technique used, namely purposive sampling. This research has 2 classes as a sample. The number of respondents was 72 students. It is divided into an experimental class and a control class. The data collection techniques used in this study are observation, questionnaires, pretest posttest questions and documentation. The data analysis techniques in this study used validity tests, reliability tests, descriptive statistical analysis, normality tests, homogeneity tests, and hypothesis tests. The results obtained are in accordance with the researcher's calculations, there is an influence of the TikTok application on the learning interest of students at SMA Muhammadiyah 09 Kualuh Hulu, LabuhanBatu Utara Regency, North Sumatra province, This can be seen from the results of the research on the value of students' learning interest scores in experimental classes that use the TikTok application as a learning medium is higher than in the control class using the conventional method (lecture). In addition, judging from the significance value of 0.000 is less than 0.05 thus H0 is rejected and Ha is accepted. Therefore, the hypothesis states that social media has an effect on students' interest in learning.